Design, synthesis, and protein methyltransferase activity of a unique set of constrained amine containing compounds. Issue 18 (15th September 2016) - Zhou, Hao; Che, Xin; Bao, Guochen; Wang, Na; Peng, Li; Barnash, Kimberly D.; Frye, Stephen V.; James, Lindsey I.; Bai, Xu
Graphical abstract: Abstract: Epigenetic alterations relate to various human diseases, and developing inhibitors of Kme regulatory proteins is considered to be a new frontier for drug discovery. We were inspired by the known multicyclic ligands, UNC669 andUNC926, which are the first reported small molecule ligands for a methyl-lysine binding domain. We hypothesized that reducing the conformational flexibility of the key amine moiety ofUNC669 would result in a unique set of ligands. Twenty-five novel compounds containing a fused bi- or tricyclic amine or a spirocyclic amine were designed and synthesized. To gauge the potential of these amine-containing compounds to interact with Kme regulatory proteins, the compounds were screened against a panel of 24 protein methyltransferases. Compound13 was discovered as a novel scaffold that interacts with SETD8 and could serve as a starting point for the future development of PKMT inhibitors.